Biohydrogen Production From Biomass Sources: Metabolic Pathways and Economic Analysis - Ahmed, Shams Forruque; Rafa, Nazifa; Mofijur, M.; Badruddin, Irfan Anjum; Inayat, Abrar; Ali, Md Sawkat; Farrok, Omar; Yunus Khan, T. M. (Frontiers in Energy Research, 2021)
The commercialization of hydrogen as a fuel faces severe technological, economic, and environmental challenges. As a method to overcome these challenges, microalgal biohydrogen production has become the subject of growing research interest. Microalgal biohydrogen can be produced through different metabolic routes, the economic considerations of which are largely missing from recent reviews. Thus, this review briefly explains the techniques and economics associated with enhancing microalgae-based biohydrogen production. The cost of producing biohydrogen has been estimated to be between $10 GJ-1 and $20 GJ-1, which is not competitive with gasoline ($0.33 GJ-1). Even though direct biophotolysis has a sunlight conversion efficiency of over 80%, its productivity is sensitive to oxygen and sunlight availability. While the electrochemical processes produce the highest biohydrogen (>90%), fermentation and photobiological processes are more environmentally sustainable. Studies have revealed that the cost of producing biohydrogen is quite high, ranging between $2.13 kg-1 and 7.24 kg-1 via direct biophotolysis, $1.42kg-1 through indirect biophotolysis, and between $7.54 kg-1 and 7.61 kg-1 via fermentation. Therefore, low-cost hydrogen production technologies need to be developed to ensure long-term sustainability which requires the optimization of critical experimental parameters, microalgal metabolic engineering, and genetic modification.